1996
DOI: 10.1007/bf02068866
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of synthetic serum substitute versus serum as protein supplementation for mouse and human embryo culture

Abstract: SSS appears to be a superior protein source for mouse embryo growth and is as good as serum from fertile donors in promoting in vitro human embryo development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 9 publications
0
15
0
1
Order By: Relevance
“…Desai et al [3] reported that Synthetic Serum Substitute 1 with alphaMEM medium may be a good basal medium for culture of human embryos to the blastocyst stage. Tucker et al [35] demonstrated that Synthetic Serum Substitute 1 is a good protein source for the culture of mouse embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Desai et al [3] reported that Synthetic Serum Substitute 1 with alphaMEM medium may be a good basal medium for culture of human embryos to the blastocyst stage. Tucker et al [35] demonstrated that Synthetic Serum Substitute 1 is a good protein source for the culture of mouse embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Since its introduction for use in IVF laboratories, the mouse embryo assay (MEA) has been instrumental for quality control (QC) and quality improvement by establishing basic guidelines for improving human embryo growth in vitro (1)(2)(3)(4). The MEA tests mainly the in vitro developmental potential of in vivo obtained mouse zygote or twocell embryos to the blastocyst stage.…”
mentioning
confidence: 99%
“…The first difference is the presence of alpha- and beta-globulin in MRC media. Several studies have reported that the use of synthetic serum substitute containing alpha- and beta-globulin has beneficial effects during the culture of human and mouse embryos [18,20,30]. The second difference is the use of hyaluronic acid in MRC media, which is found at high concentrations in the fluid of the female reproductive tract [31-33].…”
Section: Discussionmentioning
confidence: 99%